Dose and Time-Dependent Effects of Caffeine on Cardiovascular Changes Induced by Adenosine - Lucas Braga Albino; Regina Sordi; Junior Garcia de Oliveira; Daniel Fernandes (Brazilian Archives of Biology and Technology, 2023)
Abstract Adenosine is an important regulator within the cardiovascular system and modulates various processes through four distinct G protein-coupled receptors (A1, A2A, A2B, and A3), causing hypotension and reduced renal blood flow, which contributes to ischemia tissue and organ dysfunction. Caffeine causes most of its biological effects by blocking adenosine receptors. Although caffeine is vastly used as a pharmacological tool in basic research, there is a lack of studies characterizing the caffeine doses necessary for blocking the cardiovascular effects of adenosine. Therefore, we evaluated the effect of different doses of caffeine (10, 30 and 100 mg/kg, s.c) on the cardiovascular changes induced by adenosine. In addition, the adenosine response was evaluated at different times (4 and 8 hours) after caffeine administration. The bolus injection of increasing doses of adenosine dose-dependently reduced blood pressure, renal blood flow and heart rate. The dose of 30 mg/kg was the most effective in blocking adenosine-induced cardiovascular events. However, the higher dose of caffeine (100 mg/kg) fails to block the adenosine effect on heart rate. The effect of caffeine lasts for 4 hours. Therefore, caffeine in the dose of 30 mg/kg can block the effects of adenosine for up to 4 hours. These data provide valuable information on the dose and frequency of caffeine administration for future studies in rats.